2015
DOI: 10.1007/s00170-015-7141-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction stir processing parameters on the microstructural and electrical properties of copper

Abstract: Friction stir processing (FSP) is an innovative technology, based on friction stir welding (FSW) operative principles, which can be used for changing locally the microstructure and the mechanical properties of conventional materials. In this work, the copper alloy C12200 was friction stir processed using two distinct tools, i.e. a scrolled and a conical shoulder tool, in order to promote different thermomechanical conditions inside the stirred volume, and consequently, varied post-processed microstructures. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…All the results in this section agree well with Leal et al's research findings. 10 Turning to ECAPed samples (Nos. 9 to 12, depicted in Figure 8(a) to (d)), a sharp decrease in the grain sizes was shown by microstructures.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…All the results in this section agree well with Leal et al's research findings. 10 Turning to ECAPed samples (Nos. 9 to 12, depicted in Figure 8(a) to (d)), a sharp decrease in the grain sizes was shown by microstructures.…”
Section: Microstructurementioning
confidence: 99%
“…A maximum grain refinement of 84% compared to the parent material was observed, which resulted in an increase in hardness up to 34%. Leal et al 10 studied the effect of FSP parameters on the microstructural and electrical properties of C12200 copper alloy. They found that the final hardness of the processed material strongly depends on the density of dislocations, which itself depends on the geometry of the tool.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the higher ratio of rotation speed to traverse speed decreases the dislocation density. As a result, the electrical conductivity of the processed copper increases [24].…”
Section: Influence Of Process Parametersmentioning
confidence: 99%
“…In addition, the higher ratio of rotation speed to traverse speed decreases the dislocation density. As a result, the electrical conductivity of the processed copper increases [24]. During FSW, a small tool tilt angle can form a less-defect processed region via increased axial impact loading and material flow [25].…”
Section: Influence Of Tool Geometrymentioning
confidence: 99%
“…The confinement time of the ploughed material in SSSQ tool was found to be more than for the other tools, since, the escape of ploughed material from the SSSQ tool cavity was difficult, when compared to concave shoulder tool concavity. This has favored considerable achievement in ductility with SSSQ pin profile, considering its leading to the fine grain size due to an unusual Hall-Petch effect 29 . The error bars of the tensile strength, hardness and elongation were calculated using standard deviation method as shown in Fig.…”
Section: Evaluation Of Mechanical Propertiesmentioning
confidence: 99%